Investigation of antibody-dye conjugates - Özer, Enfal. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Polymeric architectures are widely used in polymer therapeutics for both imaging and drug delivery applications. Design of these polymer drug conjugates consists of three parts: water soluble monomer, linker and the drug or imaging agent. Linkers are chosen according to the stimuli which is preferably overexpressed in the tumor environment. In addition to polymeric scaffolds, targeting agents can be introduced to these systems. As a targeted drug delivery agent, antibody drug conjugates have been used in the market recently for the treatment of cancer. Antibody ensures specific targeting of the cargo due to strong affinity to their receptors. However, these agents are limited by the number of drug molecules they can carry. To overcome this limitation, polymer is conjugated to antibody where the payload is carried by this polymer. As a model system, trastuzumab is conjugated to dye bearing polymers.
Keywords: Drug delivery systems.; Immunoglobulins.